Win shift lose stay: An experimental test of non-compete clauses - Guido Bünstorf; Christoph Engel; Sven Fischer; Werner Güth (Max Planck Institute for Research on Collective Goods, 2013)
We experimentally test the effect of enforceable non-compete clauses on working efforts. The employee can invest into the probability of making a profitable innovation. After a successful innovation (Win) the employee may want to leave the firm (Shift) whereas after an innovation failure (Lose) he may remain (Stay) . In the treatments with non-compete clause, but not in the baseline, the employer can prevent successful innovators from leaving the firm. With standard preferences, effort should be lower if the worker cannot leave the firm, except if compulsory compensation for having to stay is very high. By contrast we find no reduction in effort even if compensation is low. Employers anticipate the incentive problem and pay a higher wage which employees reciprocate by higher effort.
Keywords: L51; D21; J33; J38; 330; reciprocity; fairness; labor relations; non compete clause; non compete covenant